Daily Stress and Sleep Associations Vary by Work Schedule: A Between- and Within-Person Analysis in Nurses. (17th December 2021) - Slavish, Danica; Dietch, Jessica; Kane, Heidi; Wiley, Joshua; Yap, Yang; Kelly, Kimberly; Ruggero, Camilo; Taylor, Daniel
Abstract: Nurses experience poor sleep and high stress due to demanding work environments. Night shift work may exacerbate stress-sleep associations. We examined bidirectional associations between daily stress and sleep, and moderation by shift worker status and daily work schedule. 392 nurses (92% female, mean age = 39.54) completed 14 days of sleep diaries and actigraphy, plus daily assessments of stress and work schedule upon awakening. Nurses were classified as recent night shift workers if they worked 1+ night during the past 14 days. Greater daily stress predicted shorter diary sleep duration and lower diary sleep efficiency. Shorter diary and actigraphy sleep duration and lower diary sleep efficiency predicted higher next-day stress. Compared to recent night workers, day workers had higher stress after nights with shorter sleep. Associations did not vary by daily work schedule. Sleep disturbances and stress may unfold in a toxic cycle and are prime intervention targets among nurses.